Cloud computing : implementation, management, and security - Rittinghouse, John W.; Ransome, James F. (CRC Press, 2010)
Moving beyond grid computing, Cloud computing has the potential to change IT operations within the traditional corporate model.. It provides a low cost outsourcing alternative for companies to efficiently get their services and capabilities to market in a manner that circumvents old-school IT models used in the corporate world today. This pioneering volume outlines all the steps and provides all the technical data a manager will need to implement and manage a Cloud computing environment. It lists providers and details the technical differences between them. A complete reference, it covers security as well as legal compliance issues.